Macro-Scale Basis Functions for the Method of Moment Analysis of Large Periodic Microstrip Arrays - Cucini, A.; Maci, S. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents a hybrid numericalasymptotic technique for the analysis of large periodic microstrip arrays. In the solution of a typical array problem, both macro-scale and element-scale spatial variations of the electromagnetic quantities are encountered. For large periodic arrays, the truncated periodicity induces a macro-scale behavior that is weakly dependent on the radiating elements themselves, but strongly dependent on the array periodicity and phasing. To incorporate this global phenomena, appropriate macro-scale functions are used in the framework of a method of moment solution. These macro-functions are associated to Floquet wave induced diffracted waves and guided waves, excited at the array boundary. The properties of these functions are discussed here. The technique is applied to the simple but significant case of printed dipole array, in order to demonstrate the effectiveness of the approach.